Website quality and user satisfaction: A higher education perspective - Dian Ulhaq Qurrata A'yun; Dwi Yoga Wicaksana; Syifatil Ulya; Rheyna Jufri Sifa Zie; Hujjatullah Fazlurrahman (Universitas Sebelas Maret, 2023)
At the forefront of this digital revolution stands the omnipresent website, a virtual gateway that transcends geographical boundaries, providing us unparalleled access to information and services from anywhere on the globe. In this increasingly interconnected world, websites have become the digital storefronts and first impressions of entities, be they businesses, organizations, or individuals. Consequently, people often make swift and decisive judgments about an agency based solely on its online presence's user experience and interface design. Given how quickly the internet is developing, the online quality of an academic university website is essential to student satisfaction. This study explores the intricate relationship between student satisfaction and academic university website quality (usability quality, information quality, service interaction quality, and user satisfaction). It provides a detailed analysis of the student experience. We use multiple regression with a sample size of 104 student respondents. This study uses factual data and student input to analyze significant areas of academic university websites. The results show that user satisfaction with website quality is positively significant to user satisfaction. Repetitive interactions are more common on websites that excel in usability, accessibility, and responsiveness. We hope this research can help developers to improve academic university websites.